2006
DOI: 10.1088/0305-4470/39/29/003
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium phase transition in a non-integrable zero-range process

Abstract: Abstract. The present work is an endeavour to determine analytically features of the stationary measure of a non-integrable zero-range process, and to investigate the possible existence of phase transitions for such a nonequilibrium model. The rates defining the model do not satisfy the constraints necessary for the stationary measure to be a product measure. Even in the absence of a drive, detailed balance with respect to this measure is violated. Analytical and numerical investigations on the complete graph … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The existence of a threshold density ρ 0 at which the background density has a discontinuous jump (see (5.7)) is reminiscent of what occurs in the model studied in [21], namely a ZRP with two species of particles, and with rates such that the stationary-state measure does not have a product form. When the densities ρ (1) and ρ (2) of the two species are equal, the behaviour of the system is qualitatively the same as that of the canonical ZRP (with one species).…”
Section: Discussionmentioning
confidence: 89%
“…The existence of a threshold density ρ 0 at which the background density has a discontinuous jump (see (5.7)) is reminiscent of what occurs in the model studied in [21], namely a ZRP with two species of particles, and with rates such that the stationary-state measure does not have a product form. When the densities ρ (1) and ρ (2) of the two species are equal, the behaviour of the system is qualitatively the same as that of the canonical ZRP (with one species).…”
Section: Discussionmentioning
confidence: 89%
“…So far a discontinuous transition in a zero-range process has only been observed heuristically in a two-species system where the stationary state is not known [15]. The above features only concern the stationary measure, and for systems without L-dependence they have been shown rigorously in a general context [16].…”
Section: Differences To Previous Resultsmentioning
confidence: 99%
“…On the other hand, simple rates may lead to zero-range processes for which the stationary distribution is unknown and not of product form. For such models, a recent study revealed the possibility of a discontinuous condensation transition [31].…”
Section: Generic Examplesmentioning
confidence: 99%